2007
DOI: 10.1111/j.1600-0722.2007.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and physiological effect of dental environment sensory adaptation on children’s dental anxiety

Abstract: Dental anxiety is a serious obstacle in conventional oral healthcare delivery. A sensory adapted dental environment (SDE) might be effective in reducing anxiety and inducing relaxation. This study aimed to assess the efficacy of a Snoezelen SDE in reducing anxiety among children undergoing scaling and polishing by a dental hygienist. The Snoezelen environment consists of a partially dimmed room with lighting effects, vibroacoustic stimuli, and deep pressure. Nineteen children, aged 6-11 yr, participated in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 23 publications
6
48
0
4
Order By: Relevance
“…125 In a more extensive environmental change involving a partially dimmed room with lighting effects, vibroacoustic stimuli and consistent body pressure (a so-called Snoezelen environment), greater relaxation resulted than in a standard operatory for children undergoing a scale and polish by a dental hygienist. 118 It should be noted, however, that the literature in this area is sparse and considerably more research is required before specific recommendations can be made in relation to altering the clinic environment in order to reduce dental anxiety.…”
Section: Clinical Practice and Treatment Approaches For Managing Dentmentioning
confidence: 99%
See 1 more Smart Citation
“…125 In a more extensive environmental change involving a partially dimmed room with lighting effects, vibroacoustic stimuli and consistent body pressure (a so-called Snoezelen environment), greater relaxation resulted than in a standard operatory for children undergoing a scale and polish by a dental hygienist. 118 It should be noted, however, that the literature in this area is sparse and considerably more research is required before specific recommendations can be made in relation to altering the clinic environment in order to reduce dental anxiety.…”
Section: Clinical Practice and Treatment Approaches For Managing Dentmentioning
confidence: 99%
“…118 It has been suggested that reducing these stress-triggers is an effective procedure for managing anxious patients. 119,120 Indeed, studies have found that changing aspects of the clinic environment, including appearance and odour, can have an effect on perceived anxiety.…”
Section: Clinical Practice and Treatment Approaches For Managing Dentmentioning
confidence: 99%
“…Tactile Deep pressure was provided by a butterfly-type wrap (adapted from Shapiro, Melmed, Sgan-Cohen, Eli, & Parush, 2007), weighted with a regular pediatric dental X-ray vest. The wings wrapped around the child from shoulders to toes and provided a deep hugging pressure to produce a calming effect.…”
Section: Participantsmentioning
confidence: 99%
“…24,25 Berbagai penelitian telah mengembangkan dalam tatalaksana DFA. Intervensi musik, 26,27 modifikasi lingkungan kerja, 28,29 biofeedback, 30,31 adalah contoh beberapa penelitian yang ditujukan dalam mengurangi DFA saat perawatan gigi. Peneliti bidang psikologi sendiri telah banyak melakukan penelitian mengenai DFA sejak tahun 1980-an.…”
Section: Pembahasanunclassified